1,3-Diaminopropane - M. P. M. Marques, Universidade de Coimbra, Portugal (My University, 2002)
Inelastic Neutron Scattering spectrum of 1,3-Diaminopropane, H₂N(CH₂)₃NH₂, measured on the TOSCA instrument.
Keywords: TOSCA